Metabolizable Protein Requirements of Lactating Murrah Buffaloes (Bubalus bubalis) Fed on Silage Based Diets - Sontakke, U.B.; Kundu, S.S.; prusty, Sonali; Mondal, Gautam; Sharma, Vijay Kumar; Kumar, Muneendra (Indian Journal of Animal Nutrition, 2018)
The aim of present study was to determine the metabolizable protein (MP) requirements of lactating buffaloes fed on silage based diet. Fifteen lactating Murrah buffaloes (Bubalus bubalis) were allocated into three treatments (n=5) on the basis of milk production (7.10Â±0.40) and days in milk (118Â±5.0 d). The nutrient requirements of buffaloes were met by feeding maize silage: concentrate mixture in proportion of 60: 40 for a period of 96 days. The MP level in second treatment (Control; 11.1% on DM basis) was provided as per ICAR (2013) standards whereas in treatment one and three, MP levels were 10% lower (10% LMP) and 10% higher (10% HMP), respectively than ICAR (2013) requirements. Feeding of diets containing varying levels of MP did not affect body weight, milk production and milk composition, urinary levels of purine derivatives and microbialN production. The N intake and N excretion showed positive correlation with dietary MP content and reported highest (P